Targets of performance audit in the structure of the state financial control - M. N. Ponkratova (Путеводитель предпринимателя)
In domestic practice state financial control today, there is a need to implement a qualitatively different methodological foundations for conducting auditing activities, primarily from the point of view of preventive approaches at an early stage to identify and recognize the likelihood of violations. A definite damper domestic practice of state control was the introduction of the fundamentals of performance audit focused on the evaluation of results to ensure planned or targets.